Decorated papers in bookbinding: A proposal for the creation of metadata for its documentation. - Ntalouka, Efthalia; Kyriaki – Manesis, Daphne; Choulis, Konstantinos; Vassilakis , Costas (Journal of Integrated Information Management, 2025)
The purpose of this study is the formulation of a metadata schema that represents the structure, methods, materials and designs of 19th century bookbindings. The creation of a metadata schema contributes in systematizing the information collected regarding bookbinding, guides and organizes the information collection and management process, and facilitates search and retrieval. For each individual element of the binding process, the corresponding metadata are defined. The proposed metadata schema focuses on the representation of decorated papers used in books as covers, or parts of covers, and as endpapers. Mapping of metadata elements to Dublin Core elements is also provided, to facilitate standardization and interoperability. To achieve systematic documentation of the decorated papers and define a comprehensive and complete set of metadata, the first step was to categorize them and identify their properties. Initially, the techniques, materials, types of designs, colours, and characteristics of the papers were studied. To this end, information from similar categorizations was sourced from the literature and the internet and utilized. Best practices followed by international standards for defining metadata and types of information encoding using controlled vocabularies and rules were identified and adopted. This study presents a set of comprehensive and organized metadata elements for decorated papers, which can be used for the study and documentation of decorated papers. Today, in Greece, there have been only a few sporadic references to decorated papers, however no organized recording or systematic classification of these papers and their attributes is available. The present study constitutes the first step towards creating a metadata schema that will enable the recording, organization, management, and utilization of decorated paper information, as well as a populated database, aiming to deepen the understanding of book collection, correlate it with the spatial-temporal context of its use, and promote and disseminate the material to user communities.